The Effectiveness Of The Use Of Blended Learning Model Based On Video Tutorial Reviewed From Students' Understanding In The Basic Graphic Learning In Banyudono State Vocational School - Abu Hamas; Dwi Maryono; Agus Efendi (Pendidikan Teknik Informatika dan Komputer, Universitas Sebelas Maret, 2019)
This study aims to determine (1) Is there a difference in students' cognitive understanding of the blended learning model based on video tutorials and conventional learning; (2) Is the use of video tutorial based blended learning models more effective than conventional learning on basic graphic design subjects. This study uses a quasi-experimental design method with a pretest-posttest control group design model. The population in this study were students of class X TKJ 1 and X TKJ 2 SMK Negeri 1 Banyudono. The sample used was 71 people. The sampling technique used is non-probability sampling. Data collection techniques using pretest-posttest and observation sheets. Data analysis techniques used are the balance test, normality test, homogeneity test, and hypothesis testing using an independent sample t-test. The results of the study are as follows. First, First, there are differences in students' cognitive understanding of video tutorial based blended learning models with conventional learning. secondly, the blended learning model based on video tutorials has a higher effectiveness compared to conventional learning on the learning understanding of class X TKJ students in SMK Negeri 1 Banyudono